SAT0115 COGNITIVE IMPAIRMENT WAS FREQUENT IN PATIENTS WITH RHEUMATOID ARTHRITIS STARTING A BIOLOGIC, WITH SIMILAR RATES OF INHIBITION OR OVERSTIMULATION: AN ANALYSIS OF 84 PATIENTS FROM THE SARIPRO STUDY. (2nd June 2020) - Marotte, H.; Lévy-Weil, F. E.; Flipo, R. M.; Schaeverbeke, T.; Fakra, E.; Gossec, L.
Abstract : Background: While cognitive impairment is an issue for patients with rheumatoid arthritis (RA), there are few data available on its frequency and possible link with other outcomes in RA. Objectives: To assess cognitive impairment in RA and its association with RA and patients' characteristics. Methods: The SariPRO study (NCT 03449758) was a French multicenter study assessing the effects of sarilumab 200 mg on patient-reported outcomes in patients with moderately to severely active RA with an inadequate response or intolerance to conventional synthetic or biologic DMARDs. This report focuses on baseline data. The main outcome of this analysis was cognitive impairment evaluated by the cognitive sub-score of the patient-reported multidimensional assessment of mood disorders (MAThyS) scale. This sub-score is scored between 0 (i.e. feeling that thoughts occur slower) and 40 (i.e. racing thoughts) where 20 is the best state. This sub-score was analyzed by tertiles where the lowest tertile indicates general inhibition, the second tertile includes normal states, and the highest tertile indicates general excitation. In addition to the MAThyS total score and sub-scores (Cognition, Emotion, Psychomotricity, Motivation and Sense perception), age, gender, duration of RA, methotrexate use, antibody status (rheumatoid factor/ACPA positivity), fatigue (FACIT-F), anxiety /depression (HADS), as well as patient global assessment (PGA) were collected. Cognitive impairment was defined as inhibition (first tertile) and excitation (third tertile). The association between cognitive inhibition and patients' characteristics (demographic, psychological and disease activity) was estimated by univariate and multivariate logistic regression in an exploratory analysis. There was no imputation of missing data. Results: In all 84 patients were included, characteristics at baseline were as expected for an RA population initiating a biologic: mean (SD) age: 59.1 (12.3) years, 75.0% female, disease duration 10.0 (10.3) years, rheumatoid factor positivity 76.1%, ACPA positivity 81.3%, and DAS28 5.0 (1.1). The mean (SD) MAThyS cognition score was 18.2 (4.9). In the exploratory multivariate analysis, factors associated to cognitive inhibition were depression (HADS depression score ≥ 8, odds ratio, OR=3.15 [95% confidence interval, 1.16; 8.59], p=0. 025), emotion inhibition (lower tertile of the MATHYS emotion regulation: OR=4.76 [1.54; 14.28]; p=0.007) and low motivation (lower tertile of motivation: OR=4.17 [1.54; 11.11]; p=0.005). Conclusion: Cognitive impairment was frequent in this population of patients with active RA, with similar rates of cognitive inhibition and cognitive excitation. The results suggest that there may be an association between cognitive inhibition, depression, emotion dysregulation and absence of motivation. Unexpectedly, this exploratory analysis did not show an association between cognition impairment and demographic characteristics or disease activity. References: [1]Study was sponsored by Sanofi Genzyme Disclosure of Interests: Hubert MAROTTE Grant/research support from: Bristol Myers Sqibb, Lilly France, MSD, Novartis, Nordic Pharma, Pfizer, SanofiAventis, Consultant of: AbbVie, Amgen, Bristol Myers Sqibb, Lilly France, MSD, Novartis, Nordic Pharma, Pfizer, SanofiAventis, Paid instructor for: Sanofi-Aventis, Speakers bureau: Sanofi-Aventis, Florence E Lévy-Weil Employee of: Sanofi Genzyme employee, René-Marc Flipo Consultant of: Johnson and Johnson, MSD France, Novartis, Sanofi, Speakers bureau: Johnson and Johnson, MSD France, Novartis, Sanofi, Thierry Schaeverbeke: None declared, Eric Fakra Consultant of: Janssen, Lundbeck, Otsuka, Sanofi, Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB